Implementation of Legal Norms & Notaries Responsibility in the Making of a Deed of Grants - Nanda Herawati; Aryani Witasari (Sultan Agung Notary Law Review, 2021)
The making of the grant deed must be carried out in the presence of an official authorized to make the deed, this is in accordance with the provisions contained in article 1682 of the Civil Code. In the case of land grants, the deed of grant is made before or by the Land Deed Making Official (PPAT). In making the grant deed, the Notary has an important role. The notary also keeps the deed of grant that has been made. The approach method used is normative juridical. The result of this research is that the authority of the Notary in making the Deed of Grant Agreement based on the Civil Code is in Article 1666 of the Civil Code which confirms that grants can be made and Articles 1671, 1672, 1687 of the Civil Code. The implementation of the land grant agreement made by a Notary on the basis of his authority must refer to the Civil Code in formulating the clauses in the Deed of Grant Agreement. Notaries are required to keep the contents of the deed and information obtained in the exercise of my position as stated in Article 4 paragraph (2) of the UUJN, it is also explained in Article 1909 paragraph (3) of the Civil Code that anyone who because of his position, work or position according to the law, must to keep something secret.